From a female perspective: plyometric training`s impact on jump, sprint, and change-of-direction performance in adult female athletes - a systematic review and meta-analysis - Zhao, R.; Yao, J.; Dong, Y. (Frontiers in Physiology, 2025)
Research on female subjects in sports science remains insufficient, particularly regarding how plyometric training affects adult female athletes` jumping, sprinting, and change-of-direction (COD) performance. This gap has prevented definitive conclusions about the magnitude and characteristics of such performance effects. This study systematically investigates the impact of plyometric training on adult female athletes' jumping, sprinting, and COD performance. A comprehensive literature search was conducted across PubMed, Web of Science (including all databases), MEDLINE, Cochrane Central Register of Controlled Trials (CENTRAL), Embase, and SPORTDiscus, with the search time frame extending from the inception of each database to 10 May 2025. Data analysis was performed using Stata 15 software, and the methodological quality of the included studies was assessed using the PEDro scale. The results indicate that plyometric training significantly enhances the jumping performance (SMD = 0.70, p < 0.001, medium effect), sprinting performance (SMD = -0.61, p < 0.001, medium effect), and COD performance (SMD = -0.86, p < 0.001, large effect) of adult female athletes. Subgroup analysis further reveals that plyometric training significantly improves countermovement jump (CMJ; SMD = 0.84, p < 0.001, large effect), squat jump (SJ; SMD = 0.41, p = 0.046, small effect), and standing long jump (SLJ; SMD = 0.45, p = 0.031, small effect) performance, as well as sprinting performance over distances of 10 m (SMD = -0.55, p = 0.016, medium effect), 20 m (SMD = -0.55, p = 0.002, medium effect), and 30 m (SMD = -0.72, p = 0.002, medium effect). This study demonstrates that plyometric training effectively improves the jumping, sprinting, and COD performance of adult female athletes. It is recommended that coaches and athletes incorporate plyometric training into their specialized training programs to optimize sport performance and training outcomes in female athletes.